Kilka uwag o potrzebie zmian w systemie sądowej kontroli decyzji i postanowień Prezesa Urzędu Transportu Kolejowego - Gołąb, Łukasz (Kwartalnik Prawa Publicznego, 2012)
The scope of the article is the problem of judicial control over the decisions and orders issued by the President of the Rail Transportation Office. Beginning with the genesis of rail transport regulation in Poland, the article presents the legal basis for the functioning of the rail transport regulatory body as well as the standards of its judicial control resulting from relevant provisions of EU directives concerning rail transport sector. Short remarks on the administrative procedures before the President of Rail Transportation Office make up an initial point for the presentation of the main subject, i.e. the dualism of judicial control, which is – generally – carried out by administrative courts, but in some cases – listed in the Act of 28th of March 2003 on rail transport – carried out by civil courts. Analysis of current legal regulation, emphasis on the links and relations between regulatory and anti-trust regimes, as well as comparative analysis on the solutions in other network-bound sectors gave rise to a thesis, that further legislative changes in the current system of judicial control in rail transport regulation law are necessary in order to extend the catalogue of cases, in which decisions and orders of the President of Rail Transportation Office should be judicially controlled by civil courts.